Narrowing the gap between intention and behavior? An empirical study of farmers’ waste classification in China - Zhou, Yuanchun; Wei, Bin; Zhang, Ran; Zhang, Limin; Zhu, Honggen; Wen, Ting (Frontiers in Environmental Science, 2023)
The source classification of domestic waste is important for protecting China’s rural environment but this is more difficult in rural areas than in urban areas due to the characteristics of farmers in China. Based on 833 valid questionnaires in Taihu Lake Basin, this study tried to determine whether there’s a gap between farmer’s intention and behavior and how to narrow the gap. A structural model was constructed to study the classification intention, behavior and influencing factors. The results show that subjective norms, publicity and education, and classification intention are significantly related to behavior, and attitude is positively related to behavior and intention. The study found a gap between farmers' intention and behavior in rural waste classification, and publicity and education activities can effectively reduce the degree of gap between them. The findings of this study help understand the status quo of farmers' behavior and intention of waste classification and provide insights for promoting the development of rural domestic waste classification.